2024
DOI: 10.1093/plankt/fbae007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of egg sacs on the swimming performance of freshwater cyclopoid copepods

Leonid Svetlichny,
Ulrike Obertegger

Abstract: Female cyclopoid copepods carry their embryos in egg sacs that impact swimming performance until nauplii hatch. We studied kinematic parameters and mechanical energy of small routine jumps and large escape jumps of non-egg-carrying (NEC) and egg-carrying (EC) females of Mesocyclops leuckarti and Macrocyclops albidus. The drag and body acceleration costs for EC females of M. leuckarti and M. albidus during routine jumps were 28 and 40%, respectively, higher than those for NEC females moving at the same speed. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A large number of free egg sacs observed in our study suggests that favorable conditions may have prompted a shift in the behavior of Copepoda. The experimental results clearly indicated that egg sacs impair the swimming of cyclopoid females and increase the energetic costs of movement [38].…”
Section: Discussionmentioning
confidence: 93%
“…A large number of free egg sacs observed in our study suggests that favorable conditions may have prompted a shift in the behavior of Copepoda. The experimental results clearly indicated that egg sacs impair the swimming of cyclopoid females and increase the energetic costs of movement [38].…”
Section: Discussionmentioning
confidence: 93%